HUMAN TERM PREGNANCY DECIDUAL NK CELLS GENERATE DISTINCT CYTOTOXIC RESPONSES - Vieira, Ricardo de Mendonça (J Immunol, 2020)
Decidual Natural Killer cells (dNK) are the main lymphocyte population in early pregnancy decidual mucosa. While dNK decrease during pregnancy, they remain present in decidual tissues at term. 1(st) trimester dNK facilitate trophoblast invasion, provide protection against infections and were shown to have many differences in their expression of NK receptors, cytokines and cytolytic capacity compared to peripheral blood NK cells (pNK). However, only limited data is available on the phenotype and function of term pregnancy dNK. In this study, dNK from human term pregnancy decidua basalis (d.basalis) and decidua parietalis (d.parietalis) tissues were compared with pNK and 1(st) trimester dNK. Profound differences were found including: i) Term pregnancy dNK have an increased degranulation response to K562 and PMA/Ionomycin (PMA/I) but lower capacity to respond to HCMV-infected cells; ii) Term pregnancy dNK are not skewed towards recognition of HLA-C, as was previously shown for 1(st) trimester dNK; iii) Protein and gene expression profiles identified multiple differences between pNK, 1(st) trimester and term pregnancy dNK suggesting term pregnancy dNK are a distinct type of NK cells. Understanding the role of dNK throughout pregnancy is of high clinical relevance for studies aiming to prevent placental inflammatory disorders as well as maternal to fetal transmission of pathogens.